Analysis of Personal Branding Implementation by TikTok Live Hosts on Sadojo Snack Sales - Ryandho Akbari, Ashif; Nugraha, Asep Erik; Kusnadi, Kusnadi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
In today's digital era, social media has become a major platform in marketing strategies, and TikTok has emerged as one of the leading platforms used for product promotion. With its live broadcasting feature, TikTok Live offers a unique opportunity for brands to interact directly with their audiences. This study analyzes the influence of personal branding host TikTok Live on Sadojo product sales Snack. Utilizing descriptive qualitative methods, data were collected through in-depth interviews, direct observation, and document analysis of Live streaming sessions. The results showed that strong personal branding from hosts, including authentic self-image, effective communication, and warm interactions, significantly influenced audience purchasing decisions and increased sales. This study highlights the importance of personal branding strategies in building emotional connections with audiences, positively impacting customer loyalty and sales results. Keywords: Personal branding, TikTok Live, product sales.